ANALYSIS OF THE INFLUENCE OF SCHOOL PRINCIPAL MANAGERIAL COMPETENCIES ON PERFORMANCE PUBLIC HIGH SCHOOLS TEACHERS IN INDONESIA - Ilham Kamaruddin; Andi Fitriani Djollong; Akhmad Ramli; Muhamad Akbar; Azis Hakim (Jurnal Scientia, 2023)
In order to achieve good management in an organization, a manager with expertise in that field is required; this rule also holds true in the field of education, particularly in schools. The principal, who serves as the manager, is responsible for the management quality of the school. The purpose of this study is to determine how teacher performance is impacted by the principal's managerial skills. This study employed a quantitative methodology. Each of the 50 teachers that participated in the study served as the sample. A questionnaire was utilized as the data collection tool. The study can draw the conclusion that the management competency variable effects the teacher performance variable by 40% based on the results of the determination test research, with the remaining 60% being influenced by other variables that were not examined. It can be interpreted that the level of contribution of these two variables is included in the medium category